Perancangan Aplikasi Pembelajaran Aksara Lontara Dengan Metode Game Based Learning - Indra Wihanry; Phie Chyan (TEMATIKA: Jurnal Penelitian Teknik Informatika dan Sistem Informasi, 2015)
This research discusses about on lontara recognition application design with game based learning method on Android. Aiming to introduce the characters lontara to the public through the android based smartphone which can be a medium for people to acquire knowledge or information about the script lontara. This application is designed by using the method of learning by doing where users can practice how to write a script characters lontara on this application. With the research is expected to help the user to learn and recognize letters lontara. The test results lontara alphabet recognition applications using questionnaires on general society and interview people who are experts in the field of regional literature. The final results of the research in the form of recognition applications, the material features, glossary, quizzes, words of wisdom, and a writing exercise is expected to increase public interest to introduce the culture of the region, especially lontara literacy through android based smartphone.